Equipping Teacher Trainees for Formative Assessment: Training of Formative Assessment in the practices of Teacher Education programme in Kerala - Prasoon C. P., Dr. Vasumathi T. (International Journal of Modern Agriculture, 2021)
Teacher training programmes plays a significant role in developing competencies and skills which is required for effective teaching. The success of teaching in so far is determined by how far teachers are oriented towards the assessment system which makes learning in school systematic and progressive. This study aims to examine how well the student teachers are equipped towards formative assessment in the practices of teacher education programmes. Qualitative approach was used for data collection and analysis of data. The participants of the study are persons who have completed teacher training programme at master level in any of the universities in Kerala. An interview guide included question to seek the opinion of participants relating to training of formative assessment in the practices of teacher education programme during their teacher training studies. Participants are conveniently selected. The participants viewed that the present practices of training programme is not adequately equip them with theoretical and practical knowledge of formative assessment. The major finding of the study is that there is neither a full-fledged conceptual framework nor an operational system for preparing the trainees towards formative assessment. The researchers recommend that teacher training programme must be elaborative by including formative assessment as a major area in its curriculum.